1976
DOI: 10.1083/jcb.68.3.620
|View full text |Cite
|
Sign up to set email alerts
|

Control of chromosome behavior in amphibian oocytes. II. The effect of inhibitors of RNA and protein synthesis on the induction of chromosome condensation in transplanted brain nuclei by oocyte cytoplasm.

Abstract: We studied the effects of actinomycin D, ct-amanitin, puromycin, and cycloheximide on the cytoplasmic activity of maturing Rana pipiens oocytes that induces chromosome condensation in transplanted brain nuclei. Treatment of oocytes with each inhibitor suppressed the chromosome condensation induced by metaphase I oocytes to varying degrees depending upon the dose of inhibitor, despite the fact that untreated metaphase I oocytes already possessed chromosome condensation activity (CCA). Treatment of brain nuclei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 15 publications
(8 reference statements)
2
23
0
Order By: Relevance
“…Thus, it seems very likely that while nuclear material is dispensable for surface changes such as cortical maturity, it is indispensable for MPF reactivation or entry into meiosis II, in (amphibian) oocytes. In this regard, we note that, unlike normal counterparts arrested at metaphase II, mature enucleated oocytes from both amphibians and mice cannot stably condense exogenously introduced chromatin (25,40), which probably reflects a lack of (stable) MPF in such oocytes (25).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems very likely that while nuclear material is dispensable for surface changes such as cortical maturity, it is indispensable for MPF reactivation or entry into meiosis II, in (amphibian) oocytes. In this regard, we note that, unlike normal counterparts arrested at metaphase II, mature enucleated oocytes from both amphibians and mice cannot stably condense exogenously introduced chromatin (25,40), which probably reflects a lack of (stable) MPF in such oocytes (25).…”
Section: Discussionmentioning
confidence: 99%
“…8 Chromosomes condensed to a metaphase state from brain nuclei injected into a maturing oocyte with MPF (Ziegler and Masui, 1976a). 8 Chromosomes condensed to a metaphase state from brain nuclei injected into a maturing oocyte with MPF (Ziegler and Masui, 1976a).…”
Section: The Ubiquitous Role Of Mpf In the Control Of Nuclear Activitymentioning
confidence: 99%
“…The latter two pathways can be uncoupled from the meiotic maturation process, and cooperate with each other to develop the DNA-replication inducing activity during MI, which will probably play an essential role in initiating S phase after fertilization. However, in Rana pipiens oocytes, it has been reported that transcriptional inhibition prevents chromosome condensation (15). As we did not perform cytological analysis, it is possible that transcription during early MI is also required for chromosome condensation in Xenopus oocytes.…”
Section: Discussionmentioning
confidence: 82%
“…During maturation, protein expression is mostly regulated at the translational level (7, 9 -11) by polyadenylation of the pre-existing mRNAs (12), or by unmasking translationally silent mRNAs (13). Inhibition of transcription has little effect on activation of MPF and initiation of meiotic maturation in response to PG (10,14,15). Therefore, although relatively high levels of transcription (mostly of rRNA) occur during MI (16,17), this has been assumed simply to enable enough RNA to accumulate for early embryonic development.…”
mentioning
confidence: 99%